Self‐organising cluster‐based cooperative load balancing in OFDMA cellular networks1. Issue 7 (21st July 2013) - Xu, Lexi; Chen, Yue; Chai, Kok Keong; Schormans, John; Cuthbert, Laurie
Abstract Mobility load balancing (MLB) redistributes the traffic load across the networks to improve the spectrum utilisation. This paper proposes a self‐organising cluster‐based cooperative load balancing scheme to overcome the problems faced by MLB. The proposed scheme is composed of a cell clustering stage and a cooperative traffic shifting stage. In the cell clustering stage, a user‐vote model is proposed to address the virtual partner problem. In the cooperative traffic shifting stage, both inter‐cluster and intra‐cluster cooperations are developed. A relative load response model is designed as the inter‐cluster cooperation mechanism to mitigate the aggravating load problem. Within each cluster, a traffic offloading optimisation algorithm is designed to reduce the hot‐spot cell's load and also to minimise its partners' average call blocking probability. Simulation results show that the user‐vote‐assisted clustering algorithm can select two suitable partners to effectively reduce call blocking probability and decrease the number of handover offset adjustments. The relative load response model can address public partner being heavily loaded through cooperation between clusters. The effectiveness of the traffic offloading optimisation algorithm is both mathematically proven and validated by simulation. Results show that the performance of the proposed cluster‐based cooperative load balancing scheme outperforms the conventional MLB. Copyright © 2013 John Wiley & Sons, Ltd.